2018
DOI: 10.3892/ijmm.2018.3744
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin EP2 receptor: Novel therapeutic target for human cancers (Review)

Abstract: Prostaglandin E2 (PGE2) receptor 2 subtype (EP2), which is a metabolite of arachidonic acid that binds with and regulates cellular responses to PGE2, is associated with numerous physiological and pathological events in a wide range of tissues. As a stimulatory G protein‑coupled receptor, PGE2‑induced EP2 activation can activate adenylate cyclase, leading to increased cytoplasmic cAMP levels and activation of protein kinase A. The EP2 receptor can also activate the glycogen synthase kinase 3β and β‑catenin path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 111 publications
1
41
0
Order By: Relevance
“…Prostaglandin (PG) A 2 , one of cyclopentenone PGs (cyPGs), is produced from PGE 2 by non-enzymatic dehydration. In contrast to PGE 2 , which acts through its cognate receptor in the cytoplasmic membrane [8,9], PGA 2 directly transports to the nucleus, where it induces de novo synthesis of proteins on which the biological functions of PGA 2 are dependent [8]. Many research groups have reported that PGA 2 affects various biological processes such as differentiation of leukemic cells, cell cycle progression and induction of apoptosis in various cancer cell lines, including hepatocellular carcinoma, breast cancer, cervical cancer, and leukemia [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Prostaglandin (PG) A 2 , one of cyclopentenone PGs (cyPGs), is produced from PGE 2 by non-enzymatic dehydration. In contrast to PGE 2 , which acts through its cognate receptor in the cytoplasmic membrane [8,9], PGA 2 directly transports to the nucleus, where it induces de novo synthesis of proteins on which the biological functions of PGA 2 are dependent [8]. Many research groups have reported that PGA 2 affects various biological processes such as differentiation of leukemic cells, cell cycle progression and induction of apoptosis in various cancer cell lines, including hepatocellular carcinoma, breast cancer, cervical cancer, and leukemia [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…When EP2 forms a complex with β-arrestin it can also function in a G protein-independent manner (Chun et al 2009). With β-arrestin as a regulator EP2 can inaugurate pathways of PI3K, Akt, proto-oncogene tyrosine-protein kinase Src, extracellular signal-regulated kinases, c-Jun N-terminal kinases and epidermal growth factor receptors (Sun and Li 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The Gα activation of the EP2 receptor can result in increased cAMP levels and activation of protein kinase A which regulates downstream transcription factors such as cAMP response element-binding protein (Fujino et al 2005 ). Direct binding of Gα to regulator of G protein signalling promotes the release of glycogen synthase kinase-3β (GSK-3β) resulting in the activation of β-catenin pathway, which triggers the transcription of genes such as c-myc, cyclin d1 and vascular endothelial growth factor (Vaid et al 2015 ). However, activation of serine/threonine-specific kinase (Akt) via Gβγ and phosphoinositide-3-kinase (PI3K) results in the inactivation of GSK-3β (Castellone et al 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…NF-kB constitutively activated by US28 also converges toward VEGF secretion by several pathways. One of them is by increased expression of cyclooxygenase-2 (COX-2), a key mediator of inflammation by its production of prostaglandin E2 (PGE2) [ 80 ] and a major determinant in several forms of cancer, as demonstrated in NIH-3T3 stably expressing US28 and in HCMV-infected human foreskin fibroblast BJ cells [ 26 ] ( Figure 2 ). Hence, treatment with Celecoxib, a COX-2 selective inhibitor, has been shown to significantly reduce tumour formation in a murine model of mice injected with US28-transfected NIH-3T3 cells by repressing the US28-induced angiogenic activity.…”
Section: The Constitutive Activity Of Us28 As a Factor Promoting Cancmentioning
confidence: 99%